2010
DOI: 10.1007/s11010-010-0702-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of cardiac isoform of alpha-2 macroglobulin in diabetic myocardium

Abstract: Earlier studies from one of the investigator's laboratory have demonstrated the presence of a high molecular weight protein (182 kDa) in the blood serum of laboratory animals subjected to pressure-induced cardiac hypertrophy and suggested that this protein may be involved in the development of cardiac hypertrophy. Studies have shown that this protein is also involved in earlier stages of cardiac complications associated with diabetes, but the role of this protein in diabetic heart is less understood. So we aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…To date, no study had reported a correlation between saliva levels of A2MG and percentage of HbA1. Studies performed by Takada and Soman et al [ 9 , 16 ] have shown similar results; however, the levels of A2MG were detected only in blood. Presently, emerging biotechnologies are advancing our knowledge of biomarkers and there is sufficient evidence establishing that the majority of compounds found in blood may also be found in saliva [ 6 ].…”
Section: Discussionsupporting
confidence: 58%
“…To date, no study had reported a correlation between saliva levels of A2MG and percentage of HbA1. Studies performed by Takada and Soman et al [ 9 , 16 ] have shown similar results; however, the levels of A2MG were detected only in blood. Presently, emerging biotechnologies are advancing our knowledge of biomarkers and there is sufficient evidence establishing that the majority of compounds found in blood may also be found in saliva [ 6 ].…”
Section: Discussionsupporting
confidence: 58%
“…Polyphenols also exert hypoglycemic effects (Sowmya et al, 2010). Serum glucose levels are affected by dietary carbohydrates, and thus maintenance of proper serum glucose concentrations is important for human health.…”
Section: ( + ) -C a T E C H I N H A D N O S U C H A C T I V I T Y Wmentioning
confidence: 99%
“…In the small intestine, the digestion of carbohydrates is regulated by α-glucosidase, and the resulting monosaccharides are transported across intestinal cells via glucose transporters. It is well known that oral administration of tea-, fruit-, and medicinal plant-extracts with maltose and starch suppressed postprandial hyperglycemia in rats and humans (Sowmya et al, 2010;Fadzelly et al, 2006;Deguchi et al, 2010;Ndong et al, 2007). One of the reasons for this effect is that polyphenols inhibit α-amylase and α-glucosidase activities (Tsujita et al, 2013;Adisakwattana et al, 2011;Gu et al, 2011;Ma et al, 2010); another is that polyphenols inhibit glucose transport via its transporter (Ovádi et al, 2005;Kobayashi et al, 2000).…”
Section: ( + ) -C a T E C H I N H A D N O S U C H A C T I V I T Y Wmentioning
confidence: 99%
“…[7] and Soman et al . [8] have shown that increased levels of A2MG in blood of diabetic patients. There is sufficient evidence establishing that the majority of compounds found in blood may also be found in saliva.…”
Section: Discussionmentioning
confidence: 99%